Importance of dynamics in the finite element prediction of plastic damage of polyethylene acetabular liners under edge loading conditions. (September 2021) - Jahani, Faezeh; Etchels, Lee W.; Wang, Lin; Thompson, Jonathan; Barton, David; Wilcox, Ruth K.; Fisher, John; Jones, Alison C.
Highlights: Dynamic finite element model for hip replacement damage under edge loading. Shown that static, rigid model is sufficient for bulk kinematics and test planning. Inertial effects required for prediction of plastic strain accumulation during heel strike. Future use for evaluating liner design changes, bearing resilience under edge loading. Abstract: After hip replacement, in cases where there is instability at the joint, contact between the femoral head and the acetabular liner can move from the bearing surface to the liner rim, generating edge loading conditions. This has been linked to polyethylene liner fracture and led to the development of a regulatory testing standard (ISO 14242:4) to replicate these conditions. Performing computational modelling alongside simulator testing can provide insight into the complex damage mechanisms present in hard-on-soft bearings under edge loading. The aim of this work was to evaluate the need for inertia and elastoplastic material properties to predict kinematics (likelihood of edge loading) and plastic strain accumulation (as a damage indicator). While a static, rigid model was sufficient to predict kinematics for experimental test planning, the inclusion of inertia, alongside elastoplastic material, was required for prediction of plastic strain behaviour. The delay in device realignment during heel strike, caused by inertia, substantially increased the force experienced during rim loading (e.g. 600 N static rigid, ∼1800 N dynamic elastoplastic, in one case). The accumulation of plastic strain is influenced by factors including cup orientation, swing phase force balance, the moving mass, and the design of the device itself. Evaluation of future liner designs could employ dynamic elastoplastic models to investigate the effect of design feature changes on bearing resilience under edge loading.